2014
DOI: 10.3109/13880209.2014.937503
|View full text |Cite
|
Sign up to set email alerts
|

Antidiabetic and antioxidant potency evaluation of different fractions obtained fromCucumis prophetarumfruit

Abstract: Context: Cucumis prophetarum Linn. (Cucurbitaceae) fruit is used for inflammatory-related problems and is proved to be possessing anticancer and hepatoprotective effects. Objective: The present investigation was to study the effect of different fractions of C. prophetarum on antidiabetic and antioxidant activity. Materials and methods: Aqueous crude extract (CE) of C. prophetarum fruits was fractionated into water soluble fraction 1 (F1), chloroform fraction 2 (F2), basic fraction 3 (F3), and neutral fraction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
2
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 22 publications
3
2
0
1
Order By: Relevance
“…The presence of a singlet methyl signal at δ H 2.02 in 1 H NMR spectra and two carbon signals at 21.9 and 170.3 in 13 C NMR spectra indicated the presence of an acetate moiety at C-25. The above data indicated the presence of a cucurbitacin tetracyclic triterpene skeleton; a comparison of the data with those published [ 10 , 12 – 14 ] indicated that structure 2 was characterized as cucurbitacin B. Further confirmation of compound 2 was achieved by comparison with an authentic sample of cucurbitacin B from our lab.…”
Section: Resultssupporting
confidence: 69%
See 1 more Smart Citation
“…The presence of a singlet methyl signal at δ H 2.02 in 1 H NMR spectra and two carbon signals at 21.9 and 170.3 in 13 C NMR spectra indicated the presence of an acetate moiety at C-25. The above data indicated the presence of a cucurbitacin tetracyclic triterpene skeleton; a comparison of the data with those published [ 10 , 12 – 14 ] indicated that structure 2 was characterized as cucurbitacin B. Further confirmation of compound 2 was achieved by comparison with an authentic sample of cucurbitacin B from our lab.…”
Section: Resultssupporting
confidence: 69%
“…Cucurbitacin (B, E, I, O, P and Q1); dihydrocucurbitacin (D and E), isocucurbitacin (B, D and E) and dihydroisocucurbitacin (D and E) have been reported to be isolated from Cucumis prophetarum L. Cucurbitacin B and Dihydrocucurbitacin B isolated from Cucumis prophetarum L., were studied for their cytotoxic activity towards human cancer cell lines, mouse embryonic fibroblast (NIH3T3) and virally transformed form (KA3IT) cells [ 9 ]. Recently the antidiabetic and antioxidant activity of the different fractions of fruits of Cucumis prophetarum L. has been reported [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…IC 50 is calculated as antioxidant or α ‐amylase inhibition concentration required to reduce the DPPH or α ‐amylase concentration by 50%. Consequently, the lower IC 50 value means the higher antioxidant or α ‐amylase inhibitory activity 38–40 . The correlation study confirmed the activity of plant extracts through chemical derivatisation.…”
Section: Resultssupporting
confidence: 58%
“…Consequently, the lower IC 50 value means the higher antioxidant or α-amylase inhibitory activity. [38][39][40] The correlation study confirmed the activity of plant extracts through chemical derivatisation.…”
Section: Bioassay-guided High-performance Thin-layer Chromatographysupporting
confidence: 54%
“…Moreover, as cited by Abdulrhman Alsayari et al, 2018 the antidiabetic and antioxidant activity of the different fractions of fruits of Cucumis prophetarum L has been reported [16].…”
Section: Introductionmentioning
confidence: 87%